2017
DOI: 10.3389/fpls.2017.01734
|View full text |Cite
|
Sign up to set email alerts
|

Events Associated with Early Age-Related Decline in Adventitious Rooting Competence of Eucalyptus globulus Labill

Abstract: The development of adventitious roots is affected by several factors, including the age of the cutting donor plant, which negatively affects rooting capacity. Eucalyptus globulus quickly loses rooting capacity of cuttings as the donor plant ages, although the molecular and biochemical mechanisms behind this process are still unclear. To better understand the bases of rooting competence loss in E. globulus, the time required for a significant decline in rhizogenic ability without exogenous auxin was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…These indicated that the inhibitory effect of GABA on AR formation is conserved between AR-recalcitrant and easy-toroot species, and also between woody perennial and annual herbaceous plants. However, the findings might not be sufficient to completely explain the adult-phase-specific rooting recalcitrance because of several adult-phase soft-wood cuttings are difficult-to-root or rooted very poorly regardless of auxin application (Diaz-Sala et al 2010;Xiao et al 2014;Aumond et al 2017;Xu et al 2017). GABA application did not mimic this serious AR recalcitrance in both Mx-J and tobacco.…”
Section: Discussionmentioning
confidence: 86%
“…These indicated that the inhibitory effect of GABA on AR formation is conserved between AR-recalcitrant and easy-toroot species, and also between woody perennial and annual herbaceous plants. However, the findings might not be sufficient to completely explain the adult-phase-specific rooting recalcitrance because of several adult-phase soft-wood cuttings are difficult-to-root or rooted very poorly regardless of auxin application (Diaz-Sala et al 2010;Xiao et al 2014;Aumond et al 2017;Xu et al 2017). GABA application did not mimic this serious AR recalcitrance in both Mx-J and tobacco.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, genomic prediction models based on DL and BRNN were investigated to predict complex traits in two economically important plant species: Eucalyptus globulus Labill. and Zea mays L. E. globulus is one of the most widely planted hardwood tree species in temperate regions of the world, mostly used as raw material for pulp and paper industry due to its highquality cellulose pulp, low lignin, and lipid content (Aumond et al, 2017). This species is also used for the production of essential oils in the pharmaceutical industry (Shao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rooting recalcitrance in difficult‐to‐root species of Eucapylptus has also been associated with relatively lower cambium‐auxin content and higher specific expression of rooting inhibitory genes, as compared to easy‐to‐root species (De Almeida et al ). The modification of auxin concentration and sensitivity during early age‐related decline in rooting competence of Eucalyptus globulus young seedlings has been described (Aumond Jr. et al ). Additionally, donor plants from this species treated with specific light quality yielded microcuttings showing higher rooting capacity than nontreated controls (Ruedell et al ).…”
Section: Introductionmentioning
confidence: 99%